2002
DOI: 10.1308/135576102322527829
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Geographical Information Systems in Examining Variations in Sociodemographic Profiles of Dental Practice Catchments: A Case Study of a Swansea Practice

Abstract: We conclude by drawing attention to wider benefits of such software tools in the dental profession and outline a research agenda to take these issues further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The accepted limitations of GIS studies have been documented. 13,14 Analysis of the missing data showed similar trends to the overall sample suggesting that the missing data did not create any bias in the results.…”
Section: Discussionmentioning
confidence: 75%
“…The accepted limitations of GIS studies have been documented. 13,14 Analysis of the missing data showed similar trends to the overall sample suggesting that the missing data did not create any bias in the results.…”
Section: Discussionmentioning
confidence: 75%
“…Increased travel time to receive specialty care for such illnesses is a potentially reversible determinant of adverse outcomes, and several studies have shown that increased distance between the patient's residence and the closest relevant medical specialist is associated with adverse outcomes (9 -12). Even within a relatively small geographic area, shorter distances to healthcare services and availability of such services at the nearest center were strongly related to increased utilization of healthcare and better outcomes (12)(13)(14)(15)(16)(17)(18)(19)(20). Given that geography is a potentially reversible barrier to accessing healthcare services, careful planning to optimize the placement of future healthcare facilities with the goal of enhancing service and improving healthcare outcomes for remote dwellers is critical.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has witnessed increased use of geographic information systems (GIS) analysis for measuring access to health services and facilities, healthcare utilization, and relationships with healthcare outcomes (6,7,9,12,(21)(22)(23)(24). However, the use of GIS techniques to determine the optimal location of a healthcare facility with the goal of optimizing patient access is limited (12,18,20,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's health planners aim at developing health policy and services that address geographic and social inequalities in health, and therefore should benefit from evidence-based approaches that can be used to investigate spatial aspects of health policy and practice, and evaluate geographic equity (or inequity) in health service provision [15]. …”
Section: Introductionmentioning
confidence: 99%